The Effect of Islamic Counseling on the Mental Health of Underprivileged Senior High School Students - Riska Hariyandani; Sahrul Sahrul (Al-Qalam Institue, 2026)
This study critically examines the use of Islamic counseling in improving the mental well-being of underprivileged students at senior high school. The main problem lies in the students' psychological vulnerability due to economic pressures that impact anxiety, low self-confidence, and emotional instability. This study used a descriptive design with a qualitative approach. Data collection techniques through in-depth interviews, observation, and documentation of the Guidance and Counseling teacher and two students selected by purposive sampling. Data analysis was carried out through reduction, presentation, and drawing conclusions with triangulation of sources and techniques. The results of the study indicate that Islamic counseling that integrates the values of patience, tawakal, gratitude, and sincerity is significantly able to reduce anxiety, strengthen emotional control, and build a positive self-concept of students. A spiritual approach based on the Qur'an and Sunnah has proven effective in fostering mental resilience and self-acceptance of family economic conditions. It is concluded that Islamic counseling is a strategic and effective intervention in improving the mental well-being of underprivileged students through an integrated strengthening of spiritual, emotional, and cognitive dimensions and the formation of a positive self-meaning on an ongoing basis